Coupling and Decoupling between Brain and Body Oscillations. (15th October 2019) - Rassi, Elie; Dorffner, Georg; Gruber, Walter; Schabus, Manuel; Klimesch, Wolfgang
Highlights: 1:4 frequency relationship between heart rate and breathing frequency both during wakefulness and sleep. 1:8 frequency relationship between heart rate and alpha frequency during task performance but not during eyes-closed rest. 1:32 frequency relationship between breathing frequency and alpha frequency during task performance but not during eyes-closed rest. Irrational frequency relationship between spindle frequency and heart rate as well as spindle frequency and breathing frequency during sleep – suggesting decoupling. Abstract: Cross frequency coupling is used to study the cross talk between brain oscillations. In this paper we focus on a special type of frequency coupling between brain and body oscillations, which is reflected by the numerical ratio (r) between two frequencies (m and n; n > m). This approach is motivated by theoretical considerations, indicating that during alert wakefulness brain-body oscillations form a coupled hierarchy of frequencies with integer relationships that are binary multiples (r = n:m = 1:2, 1:4, 1:8…..). During sleep we expect an irrational relationship (r = n/m = irrational number) between brain and body oscillations that reflects decoupling. We analyzed alpha frequency, heart rate, breathing frequency during performance of a memory tasks and in addition spindle frequency from data collected by the SIESTA sleep research group. As predicted, our results show a binary multiple frequency relationship between alpha, heart rate and breathing frequency during task performance but an irrational relationship between spindle frequency, heart rate and breathing frequency during sleep.